Lung Function After Stereotactic Body Radiation Therapy for Early-Stage Non-Small Cell Lung Cancer, Changes and Predictive Markers - Berg, Janna; Ramberg, Christina; Haugstvedt, Jon Olav Sulheim; Bengtson, May-Bente; Gabrielsen, Anne-Marie; Brustugun, Odd Terje; Halvorsen, Ann Rita; Helland, Åslaug (Frontiers in Oncology, 2021)
Introduction: The present study explores changes in pulmonary function, symptoms and radiological signs of pneumonitis after curatively intended stereotactic body radiation therapy (SBRT). Methods: All inoperable, early-stage non-small cell lung cancer patients treated with stereotactic body radiation therapy (SBRT) from 2014-2017 were included in this single-centre study. They were followed regularly for 12 months after treatment. The patients were classified into three groups based on radiology and symptomatology: no radiation pneumonitis, asymptomatic and symptomatic radiation pneumonitis. Results: Forty-four patients with stage IA-IIB disease were treated with 45–56 Gy in 3–8 fractions. The median age was 75 years, 43% of the patients were female; 60% of the patients had a COPD in GOLD grade of 2-4, and 95.5% were active or former smokers. Symptomatic radiation pneumonitis occurred in 18% of the patients and asymptomatic pneumonitis as defined by radiology, in 39%. The mean of forced expiratory volume in 1 second (FEV1) and diffusion capacity for carbon monoxide (DLCO) decreases for all patients during the first years were higher than one would expect from physiologic ageing. FEV1 and DLCO in percent decrease 7-8 % at 1-1.5 months in the symptomatic radiation pneumonitis group. CT scan findings consistent with radiation pneumonitis occurred after a median of 2.9 months in the symptomatic and 5.4 months in the asymptomatic radiation pneumonitis groups. In the group with symptomatic radiation pneumonitis, symptoms, as measured by the Clinical COPD questionnaire score, significantly increased at 3 and 6 months. Significant higher maximum doses to the critical lung volumes DC1000cm3 (1000 cm3 of lung receiving a given dose or less) and DC 1500cm3 (1500 cm3 of lung receiving a given dose or less) were observed in patients who developed radiation pneumonitis. Conclusion: Early decrease in measured FEV1 and DLCO occurred before imaging changes and symptoms and might indicate the development of symptomatic radiation pneumonitis. The dose to critical lung volumes of DC1000 cm3 and DC1500 cm3 can predict the risk for the development of symptomatic radiation pneumonitis.